Role Of Hematopoetic Stem Cell In Inflammatory Response During Orthodontic Tooth Movement : A Narrative Review - Dwi Rahmawati, - (DR. P. R. YADAV, 2020)
The basic concept of Orthodontic Tooth Movement (OTM) for orthodontists is always interesting and important to know so that it can determine strategies to reduce orthodontic treatment time. The purpose of this narrative review is to describe the role of Hematopoietic Stem Cells (HSCs) in the inflammatory response during OTM as well as the blood circulation system during OTM. OTM can stimulate the biological response from periodontal tissue after orthodontic force is given. The resulting response during OTM was the remodelling of periodontal ligament and alveolar bone. OTM involves various chemical mediators including chemokines, cytokines, prostaglandins and bone cells such as osteoblasts and osteoclasts. HSCs are multipotent cells that play an important role during inflammation through the blood circulation system. OTM stimulates sterile inflammation that causes HSCs migration to injury area. HSCs are thought to have an important role during OTM by regulating inflammation so further research is needed on this matter.